GENESIS OF SOCIAL MEMORY (Conferencea, 2023)
The article provides information about historical consciousness, which is an important element of the forms of social consciousness that determines and implements the continuity of generations in the continuity of historical processes, and the national memory created through it. In the period of intensification of globalization processes, the historical thinking of the people of the younger generation reveals the current state of the socialization of history and the current level of social memory formed on this basis.